The Art of Dwelling - Lorentzen, Jakob Due (AU Library Scholarly Publishing Services, 2025)
The dissertation advances a contemporary thinking of dwelling referred to as the art of dwelling based on a thematic reading of the concept of dwelling in Martin Heidegger’s late works. The investigation is informed by Heidegger’s 1962 journey to Greece and his resulting travel book, Aufenthalte (Sojourns). These serve as a structuring prism for exploring Heidegger’s late reflections on place and experience, which come to a head in the encounter with the ancient Greek artifacts and landscape. The study opens with an investigation of the concept of dwelling [wohnen] understood as a composite term (in chapter 1). In order to appreciate the full experiential activity of dwelling, the conventional notion of wohnen is expanded to incorporate Heidegger’s notions of verweilen and aufhalten, so that the spatial [wohnen], the temporal [weilen], and the experiential [aufhalten] aspects of the term all come to the fore in a thematic reading of Sojourns and other late writings of Heidegger. Reflected in Sojourns is also an overarching discussion of homelessness and dwelling, as well as an examination of Heidegger’s thinking of technology and the history of being as conditions for the inquiry (in chapter 2). The exposition of dwelling as a composite term has implications for the notion of place. Following an examination of how dwelling presupposes a sense of place and an ontology of atmosphere in Sojourns and in the late Heidegger more generally (in chapter 3), the study brings these intertwining concepts into conversation with contemporary perspectives. What emerges from Heidegger’s findings in Sojourns on the sense of place, and his thinking on sculpture (in chapter 5) in terms of spatiality and dwelling, is the key concept of receptivity in relation to dwelling. In this way, Heidegger’s thinking on place is brought into conversation with contemporary modern art and literature, motivating a reappropriation of the notion of place. Following these lines of development, the study advances a contemporary thinking of dwelling referred to as the art of dwelling (in chapter 6) as a mode of being in the world. The study finds renewed potential for a thinking of place, atmosphere, and embodied experience today by calling attention to the activity of the Aufenthalt and the concept of atmosphere reflected in dwelling as a sensitivity toward the singularity of the world.